The effectiveness of pop-up book media in learning reading skills of grade 2 elementary school - Sunarti Sunarti; Deri Anggraini; Desy Putri Sarie; Padrul Jana (LPMPP Universitas Negeri Yogyakarta, 2023)
This quasi-experimental study aims to test the effectiveness of Pop Up Book media in learning reading skills in grade II Elementary School. Randomly class II B was assigned as an experimental class, taking reading lessons using Pop Up Book media, and class II-A, as a control class, participating in reading lessons using ordinary picture media. Data collection techniques use performance tests to assess 6 aspects of reading skills, namely accuracy in voicing writing, pronunciation reasonableness, intonation, fluency, voice clarity, and word understanding. The validity of the test items ranged from 0.65 – to 0.70, with a reliability index of 0.704. The average value of reading skills from the experimental class students' pre-test results was 63.96, and 62.29 in the control class students. From the different test results, the pretest score obtained a t value of 0.887 at sig. 0.380. It can be concluded that there is no difference in reading skills between the two groups before the treatment was carried out. After the learning was carried out, the average post-test scores of the experimental class students were 81.56 and 65.38. control class students. The results of hypothesis testing obtained a value of t 7,252 on s ig. 0.000. It can be concluded that there is a very significant difference in reading skills between the experimental class and the control class. The results of the study concluded that the Pop Up Book media was effective for improving the reading skills of second-grade elementary school students.